Confronting Online Extremism: The Effect of Self-Help, Collective Efficacy, and Guardianship on Being a Target for Hate Speech. (October 2017) - Costello, Matthew; Hawdon, James; Ratliff, Thomas N.
Who is likely to be a target of online hate and extremism? To answer this question, we use an online survey ( N = 963) of youth and young adults recruited from a demographically balanced sample of Americans. Adapting routine activity theory, we distinguish between actor-initiated social control (i.e., self-help), other-initiated social control (i.e., collective efficacy), and guardianship and show how self-help is positively related to the likelihood of being targeted by hate. Our findings highlight how online exposure to hate materials, target suitability, and enacting social control online all influence being the target of hate. Using social networking sites and encountering hate material online have a particularly strong relationship with being targeted with victim suitability (e.g., discussing private matters online, participating in hate online) and confronting hate also influencing the likelihood of being the target of hate speech.